(untitled) (Bangladesh Rice Journal, 2026)
Sheath blight (ShB), caused by Rhizoctonia solani AG1-IA, is a globally devastating rice disease resulting in 20–50% yield losses. Its management is challenged by the pathogen’s genomic complexity, quantitative host resistance, and trade-offs with agronomic traits. We first discuss the critical foundation of reliable phenotyping, spanning standardized field assays to emerging high-throughput phenomics, which is essential for accurate genetic dissection. This review also synthesizes advances in genetic and molecular dissection of ShB resistance, emphasizing the transformative role of Genome-Wide Association Studies (GWAS). We highlight how GWAS has overcome limitations of traditional QTL mapping, enabling high-resolution discovery of major resistance loci (e.g., SBRR1), defense pathways (e.g., ROS-antioxidant systems), and novel candidate genes across diverse germplasm. Integration of GWAS with gene editing (e.g., dep1-cys), overexpression strategies (e.g., OsCSP41b), and transcription factor networks (e.g., OsbHLH34, OsBZR1) reveals pathways to break yield-resistance trade-offs. Future progress hinges on multi-omics-augmented GWAS, epistasis modeling, and deploying genomic selection for durable resistance. This work underscores GWAS as a cornerstone for accelerating ShB-resistant rice breeding. Bangladesh Rice J.28(2): 25-37, 2024